ON THE QUESTION OF THE DEVELOPMENT OF FETAL CONGENITAL MALFORMATIONS IN THE CONDITIONS OF PREVENTIVE USE BY MOTHERS OF FOLIC ACID IN THE PERINATAL PERIOD - I. A. Toropova; R. N. Alyautdin; O. S. Alyautdina; B. K. Romanov (Безопасность и риск фармакотерапии)
Neural tube defect relates to congenital defects caused by folic acid deficiency or violation of its exchange. Prophylactic administration of folic acid by pregnant women has greatly reduce the incidence of these malformations. However, despite preventive measures, reports of such serious adverse events continue to be recorded. The analysis showed that one of the possible causes of malformations may be the presence of the polymorphism of the gene encoding 5, 10-methylenetetrahydrofolate. The effect of this mutation on the metabolism of folic acid and possible recommendations to patients are discussed.